Compact Four-Element Phased Antenna Array for 5G Applications - Muhammad Kamran Ishfaq; Tharek Abd Rahman; Mohamed Himdi; Hassan Tariq Chattha; Yasir Saleem; Bilal A. Khawaja; Farhan Masud (IEEE Access)
This paper presents a four-element compact phased Planar Inverted-E Antenna (PIEA) array for 6 GHz beamforming applications. For compact phased arrays, the mutual coupling is a severe performance degrading factor. Therefore, three mutual coupling reduction techniques are employed, which include (i) PIEA as an array element which is a modified version of Planar Inverted-F Antenna (PIFA) by inserting another shorting plate, (ii) slots in the ground plane and (iii) two slits in each etched ground slot. With these techniques, the mutual coupling is reduced below −19 dB in the operational bandwidth from 5.7 to 6.4 GHz. The compact design with an inter-corner spacing of $0.013λ _{o}$ and an inter-element spacing of $0.3λ _{o}$ is achieved. The peak gain obtained by this compact phased array is 8.36 dBi. This array can scan up to a maximum scanning angle of ±70°. A good general agreement is found between the measured and simulated results.